2017
DOI: 10.3855/jidc.8026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, serotype distribution, and antimicrobial resistance of Salmonella isolated from food products in Morocco

Abstract: Introduction: Salmonellosis is one of the most common foodborne diseases worldwide. The irrational use of antibiotics in medicine and in animal feed has greatly promoted the emergence and spread of resistant strains of non-typhoidal Salmonella. Methodology: A total of 464 food products were collected in Tetouan from January 2010 to December 2012. The isolation and identification of Salmonella were performed according to Moroccan standard 08.0.116. All isolates were serotyped and were then tested for antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…Based on our meta-analysis, the PPE of AR against sulfonamide was 92%. Our findings correlate with other studies, which reported an increased development of AR against sulfonamide in Spain, Ghana, Central African Republic, Morocco, and Italy with 38.1% 72.4%, 29%, 25%, and 69%, respectively [ 14 , 15 , 16 , 17 , 18 ]. Sulfonamides resistance can arise from chromosomal dihydropteroate synthase (DHPS) mutations or from the acquisition of DHPS drug resistance genes, whose products have lower affinity for sulfonamides [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on our meta-analysis, the PPE of AR against sulfonamide was 92%. Our findings correlate with other studies, which reported an increased development of AR against sulfonamide in Spain, Ghana, Central African Republic, Morocco, and Italy with 38.1% 72.4%, 29%, 25%, and 69%, respectively [ 14 , 15 , 16 , 17 , 18 ]. Sulfonamides resistance can arise from chromosomal dihydropteroate synthase (DHPS) mutations or from the acquisition of DHPS drug resistance genes, whose products have lower affinity for sulfonamides [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, AMR in Salmonella spp. from foods and environmental sources was mentioned by several studies [92,93]. Such nding is also revealed by other systematic reviews in other countries [77,78].…”
Section: Discussionsupporting
confidence: 55%
“…However, AMR in Salmonella spp. from foods and environmental sources is mentioned by several studies [ 89 , 90 ]. Such finding is also revealed by other systematic reviews in other countries [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%